Major depressive disorder - Strakowski, Stephen M.; Nelson, Erik, 1964- (Oxford American psychiatry library., 2015)
Depressive disorders are among the most common conditions in the world and are the leading causes of disability, affecting millions of people. Depression is also a common secondary condition, occurring at increased rates alongside virtually any illness that impacts brain function. Because it is so common, people suffering from depression seek help from a wide variety of clinicians, including: family doctors, pediatricians, gynecologists, psychiatrists, internists, psychologists, social workers and other therapists. In fact, depression is so common that the demand for care far exceeds the avail.